A Methodological Framework for Geographic Information Systems Development. (28th June 2016) - Dean, Emma; Taylor, Mark J.; Francis, Hulya; Lisboa, Paulo; Appleton, Debbie; Jones, Mark
Abstract : Geographic information systems (GISs) provide map based spatial analyses of geo‐coded data. In this paper we examine a methodological framework for geographic information systems development that was developed and refined over a six year period based upon a fire prevention support geographic information system for a UK fire and rescue service. The methodological framework involves the use of a multi‐methodology approach that incorporates social and organizational analysis, spatial modelling, and functional design. Copyright © 2016 John Wiley & Sons, Ltd.